The Emperor's Cadlina, hidden diversity and gill cavity evolution: new insights for the taxonomy and phylogeny of dorid nudibranchs (Mollusca: Gastropoda) - Korshunova T., Fletcher K., Picton B., Lundin K., Kashio S., Sanamyan N., Sanamyan K., Padula V., Schrödl M. & Martynov A. (Zoological Journal of the Linnean Society, 2020)
Dorids are one of the largest nudibranch groups, encompassing more than 2000 species. One of the crucial problems with tracing the evolution of dorids is the relationship between cryptobranch dorids (gill cavity present) and phanerobranch dorids (gill cavity absent). Integrative morphological and molecular studies of the enigmatic Japanese dorid species of the cryptobranch genus Cadlina, C. japonica and ‘C.’ sagamiensis, which were collected by the Emperor of Japan (Shōwa era), are presented here for the first time. It is shown that while C. japonica does belong to the Cadlina clade, another Japanese species ‘C.’ sagamiensis is not part of the cryptobranch dorids of the family Cadlinidae, but is related to both the phanerobranch dorid family, Hexabranchidae, and to the cryptobranch family Cadlinellidae stat. nov. A new genus, Showajidaia gen. nov., and new family, Showajidaiidae fam. nov., are proposed for ‘C.’ sagamiensis, and four new species of the genus Cadlina are described based on a dorid-wide molecular phylogenetic analysis, which is the first substantial update of the dorid family system since 2010. Integration of phylogenetic data with an ontogenetic model of dorid evolution suggests that cryptobranch organization can be most reliably assessed as the ancestral state for the majority of dorids.
Code-compliant early view published online 20 February 2020; print version published July 2020